La ética y la discriminación laboral en el área de recursos humanos - Mina-Bone, Santos Geovanny (Editorial Grupo AEA, 2022)
Discrimination has become one of the biggest obstacles to overcome worldwide whose impact is evident even in the workplace where searches are conducted to find perfect candidates for available vacancies with criteria based on ethnic, religious or racial discrimination where many people end up losing a job opportunity due to these social stigmas. The objective of the research is to analyze the impact of ethics and labor discrimination in the area of human resources, being one of the most important departments that make up an entity, the application of objective standards for selection in the recruitment process is still largely ignored. For this reason, the research is based on a methodology of bibliographic review by compiling the most outstanding data on the subject in order to obtain relevant results with a realistic nuance. In the analysis of the results, there is a greater hiring for the male gender, being this an indicator of the inequality found in the job offers within the country, as well as the level of recruitment where gender discrimination is evident, where the male group predominates at the national level. It is concluded that Ecuador ignores the Constitution of the Republic, which states that everyone has the right to a decent job regardless of social status, gender, religion, ethnicity or sexual preference.